Real-time rendering - Moller, Tomas; Hoffman, Naty; Haines, Eric (Boca Raton, FL AK Peters, 2018)
Thoroughly updated, this fourth edition focuses on modern techniques used to generate synthetic three-dimensional images in a fraction of a second. With the advent of programmable shaders, a wide variety of new algorithms have arisen and evolved over the past few years.
Keywords: Gráficos de ordenador; Programación en tiempo real; Infografía